Sharia Fintech Dispute Resolution Formulation in the Religious Courts - Suparli, Tayep (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2023)
Cases in the financial industry began to be found, including cases related to Islamic economics. The settlement of conventional economic cases and sharia economics has a different place, according to the authority of each court. Therefore, this study aims to find a formulation of sharia fintech dispute resolution through litigation in the Religious Courts. The problem is whether the Religious Courts resolve Islamic fintech, and if so, how is the settlement process? This type of research is qualitative with the library research method and analyzed using a normative juridical approach. The study results found that fintech disputes can be resolved in Religious Courts. Settlement of disputes in religious courts can be submitted through simple or ordinary lawsuits, and trials can be carried out electronically (e-litigation) or in ordinary procedures. In conclusion, the resolution of sharia fintech disputes is the authority of the Religious Courts.